Penggunaan Bahasa pada Masyarakat Bermatapencaharian Pedagang di Pangandaran dalam Aktivitas Perdagangan - Maulana, Nanang (Universitas Mathla'ul Anwar Banten, 2018)
Languages such as land that has no end to cultivate or become the object of research by researchers, the nature of dynamic language allows researchers to find new cases or even current theories. In addition, the breadth of language studies makes language can be studied or examined from various perspectives, both from the internal or external language itself. In a study entitled “The Use of Language in Livelihoods Traders in Pangandaran in Trading Activities” this language was studied from a sociolinguistic perspective and aimed to find out or know the language usage of traders in Pangandaran in trading activities. Based on the results of the research conducted shows that a) the language usage of traders in Pangandaran tends to use their respective regional languages as proof of language revitalization or retention b) Many phonemes are used when the traders carry out their trading activities c) There is language interference d) Available code switching or mixed code among traders in Pangandaran e) Language influenced by the speakers' background, especially in this research is culture. This type of research is a qualitative descriptive research while data collection techniques in this study are literature review, observation, data collection and analysis.